A DIVA-compatible Mycobacterium bovis triple mutant vaccine confers protection against bovine tuberculosis in mouse model - Blanco, Federico Carlos; Onnainty, Renée; Marini, María Rocío; Klepp, Laura Ines; Rocha, Rosana Valeria; Villafañe, Luciana María; Vazquez, Cristina Lourdes; Canal, Ana; Granero, Gladys; Bigi, Fabiana (Elsevier, 2025)
Bovine tuberculosis (bTB) is a pulmonary infectious disease caused by Mycobacterium bovis, affecting cattle and a wide range of mammals, including humans. Despite its significant impact on global livestock production, no commercial vaccine is currently available, partly due to potential interference with standard diagnostic tests. In this study, we evaluated the protective efficacy of a triple M. bovis mutant lacking the immunodominant antigens ESAT-6 and CFP-10, as well as the virulence factor Ag85A. This mutant is compatible with DIVA (Differentiation of Infected from Vaccinated Animals) diagnostics based on ESAT-6 and CFP-10 detection. The triple mutant was assayed both alone and in a heterologous prime-boost regimen using recombinant Ag85A conjugated to chitosan nanocapsules. Protection was assessed by quantifying M. bovis colony-forming units (CFUs) in the lungs and spleen following challenge. Organ homogenates were cultured on solid media, and CFUs were enumerated at five and ten weeks post-plating. At five weeks, all vaccinated groups demonstrated comparable protection in the lungs. In the spleen, both the triple mutant and BCG groups showed reduced CFU counts compared to the un vaccinated group. By ten weeks, lung protection was most pronounced in the prime-boost and BCG groups, whereas spleen protection was restricted to the prime-boost group. At this stage, persistence of the triple mutant was detected in both lungs and spleen, highlighting the need for further evaluation of its residual virulence. Post- challenge immune responses were assessed by measuring CD4 +KLRG1-CXCL3 + T cells, a subset previously associated with protective immunity against tuberculosis, among other T cell populations evaluated. Vaccinated mice exhibited a significant expansion of this population compared to unvaccinated controls. Notably, higher frequencies of these cells correlated with reduced pulmonary bacterial burden, reinforcing their potential as a biomarker of protective immunity.